Effects of biopesticides on the management of Myzus persicae Sulzer and Phenacoccus manihoti - ESTWICK, Therola Califa; SKEETE, Analesa Olinda; FREDERICKS, David Bartholomew (Food Science and Technology, 2024)
Aphids (Myzus persicae Sulzer) and mealybugs (Phenacoccus manihoti) are two economically important pests affecting agricultural crops in Guyana. The principal mode of control is the application of synthetic insecticides, which can be prejudicial on the environment and human health. Alternatively, these pests can be controlled using plant extracts with insecticidal and repellent properties. This article highlights the effects of three plant extracts obtained from locally cultivated crops in Guyana. Gas chromatography-mass spectrometry analysis was performed to identify the chemical compounds present in each extract with high insecticidal activity against aphids and mealy bugs revealing the presence of 8, 15, and 7 chemical compounds with “eucalyptol” common to all extracts. Laboratory bioassays were conducted under environmental conditions to determine the efficacy of methanol extracts obtained from Zingiber officinale rhizome, Mentha viridis, and Jatropha curcas leaves in controlling M. persicae Sulzer and P. manihoti using the leaf dip method. Results obtained indicated that the three plant extracts were significantly (p < 0.05) toxic to M. persicae Sulzer and P. manihoti after 48 h exposure.